Factors affecting cell biomass and flavonoid production of Ficus deltoidea var. kunstleri in Cell Suspension Culture System - Zainol, Haida; Ahmad, Syahida; Syed Mohd Ariff; Mahmood, Maziah; Awang @ Mansor, Mohd Hakiman (Nature Publishing Group, 2019)
A study was conducted to establish in vitro culture conditions for maximum production of biomass and flavonoid content for Ficus deltoidea var. kunstleri, locally named as Mas Cotek, known to have a wide variety of potential beneficial attributes for human health. Size of initial inoculum, cell aggregate and initial pH value have been suggested to influent content of biomass and flavonoid for cell suspension culture in several plant species. In the present study, leaf explants were cultured by cell suspension culture procedures in MSB5 basal medium supplemented with predetermined supplements of 30 g/L sucrose, 2.75 g/L gelrite, 2 mg/L picloram and 1 mg/L kinetin with continuous agitation of 120 rpm in a standard laboratory environment. Establishment of cell suspension culture was accomplished by culturing resulting callus in different initial fresh weight of cells (0.10, 0.25, 0.50, 1.0, and 2.0 g/25 mL of media) using similar basal medium. The results showed that the highest production of biomass (0.65 g/25 mL of media) was recorded from an initial inoculum size of 2.0 g/25 mL media, whereas the highest flavonoid (3.3 mg RE/g DW) was found in 0.5 g/25 mL of media. Cell suspension fractions classified according to their sizes (500–750 µm, 250–500 µm, and <250 µm). Large cell aggregate size (500–750 µm) cultured at pH 5.75 produced the highest cell biomass (0.28 g/25 mL media) and flavonoid content (3.3 mg RE/g DW). The study had established the optimum conditions for the production of total antioxidant and flavonoid content using DPPH and FRAP assays in cell suspension culture of F. deltoidea var. kunstleri.